The status of pro-inflammatory cytokines TNF-α and IL-6 in the cerebrospinal fluid of dogs with nervous distemper - Marjan Mahmoodabadi; Hadi Mohebalian; Ali Asghar Sarchahi (BMC Veterinary Research)
Abstract Background Canine distemper virus (CDV) is a multisystemic disease in dogs that causes severe neurological signs due to viral replication in neurons and glial cells; this leads to gray matter lesions and demyelination. The resulting inflammation causes additional harm to the affected tissues. This study aimed to investigate the relationship between pro-inflammatory cytokines Tumor Necrosis Factor (TNF-α) and interleukin (IL-6) levels in Cerebrospinal fluid (CSF) and the neurological form of distemper disease in dogs. Results The study included 23 CDV-infected dogs with neurological signs, 10 diseased but CDV-negative (non-infected) dogs, and 12 healthy controls. CSF samples were analyzed using Reverse Transcription Polymerase Chain Reaction (RT-PCR) for CDV sequences and the sandwich enzyme-linked immunosorbent assay (ELISA) method for quantifying IL-6 and TNF-α levels. While a significant increase in CSF cytokine levels was observed between the CDV-infected and healthy controls, no significant differences were detected between the CDV-infected and non-infected diseased groups. Conclusions The elevated levels of IL-6 and TNF-α in the CSF of dogs with nervous distemper suggest their involvement in disease pathogenesis. However, their lack of specificity limits their use as reliable diagnostic biomarkers for distinguishing nervous distemper from other neurological conditions in dogs. Further research is needed to identify more accurate and specific biomarkers for the precise diagnosis and effective management of CDV infection.